Muatan Nilai-Nilai Moderasi Beragama dalam Buku Ajar Pendidikan Agama Islam dan Budi Pekerti SD Kelas I - Amelia Ananda; Rini Rahman (AS-SABIQUN, 2022)
This study aims to determine the content of religious moderation values in the PAI-BP SD class I textbooks. The research was conducted with a qualitative approach and using the method of content analysis. Based on the formulation of the problem, this research focuses on what moderate values are contained in the PAI-BP SD grade I textbooks?. In collecting data, researchers use documentation studies to examine and understand sources related to research problems. The data collected from various sources are then analyzed scientifically and in depth to be described. From the results of the study, the findings of the content of religious moderation values in the PAI-BP SD class I textbooks are classified into two parts, namely: 1) the content of religious moderation values in the subject matter of the textbook, and 2) the content of religious moderation values. in the textbook text. The findings of this research can later be used as initial data to carry out related research on similar themes.